A reinterpretation of Coase's land monopoly model: Locational specificity and the betterment potential of land as de jure and de facto property. (July 2019) - Lai, Lawrence W.C.; Chau, K.W.
Highlights: First in-depth neo-institutional inquiry into property boundary as planned land. First attempt to canvass Coase's rare treatises on land monopoly. Three important and well known real life examples. Abstract: On the grounds of two unique features of land, locational specificity and capacity for betterment through in-situ entrepreneurial transformation, this monograph uses three real world examples to qualify Coase's idea, mentioned in two of his works on the Federal Communications Commission (FCC), that a state monopoly of land is undesirable for allocating land due to the huge transaction costs of non-price allocation. These two features of land enable the creation of institutional arrangements constraining such costs occasioned by rent-seeking or rent dissipation envisaged by Coase. Breaking new theoretical grounds in understanding planning beyond a matter of property rights assignment and attenuation, the three examples show that where the state has an effective monopoly of land supply, it does not behave like a private land monopoly but, subject to constrained rent-seeking, enables, and also possibly brings about the betterment of land and its redistribution by government planning . The examples, two of which testify to a Coase Theorem predicated on Coase's first work on the FCC, also shed light on the question of property boundaries as an ex ante planning tool for de jure property or an ex post outcome of development. The monograph shows that the transaction costs of both dividing and recombining tradable land, as physically unitized into land parcels within a layout, are greater than partitioning and re-partitioning marketable segments of radio frequencies.